2020
DOI: 10.1186/s12891-020-03635-1
|View full text |Cite
|
Sign up to set email alerts
|

Timing for closed reduction procedure for developmental dysplasia of the hip and its failure analysis

Abstract: Background It remains controversial whether the older age to perform closed reduction (CR) procedure for developmental dysplasia of the hip (DDH), the higher incidence of complications. The aim of this study is to evaluate the midterm outcome of CR for DDH among different age groups, and to analyze and identify risk factors for the failure of this procedure. Methods Clinical data of 107 DDH patients, who received CR, were retrospecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
4
7
0
Order By: Relevance
“…The study subjects were children diagnosed with DDH who were treated at our hospital from June 2018 to June 2020. The inclusion criteria were (1) a diagnosis of completely dislocated DDH (ultrasonic examination of children less than 6 months of age showed Graft type IV or anteroposterior pelvic radiographs of children aged 6-12 months showed International Hip Dysplasia Institute type III or IV DDH); (2) a positive Ortolani sign (reduction of the femoral head to the acetabulum and detection of the bouncing sound of reduction); (3) children aged ≤12 months; (4) treatment with the Pavlik harness or manual reduction and plaster fixation (for children less than 6 months of age, the Pavlik harness was adopted; for children aged 6-12 months or those in whom the Pavlik harness failed, manual reduction and plaster fixation were performed); (5) anteroposterior pelvic radiographs and MRI of the hip joint were performed after 3 weeks of treatment with the Pavlik harness or 1 day after manual reduction and plaster fixation, and the quality of images met the requirements of the study; (6) complete data.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The study subjects were children diagnosed with DDH who were treated at our hospital from June 2018 to June 2020. The inclusion criteria were (1) a diagnosis of completely dislocated DDH (ultrasonic examination of children less than 6 months of age showed Graft type IV or anteroposterior pelvic radiographs of children aged 6-12 months showed International Hip Dysplasia Institute type III or IV DDH); (2) a positive Ortolani sign (reduction of the femoral head to the acetabulum and detection of the bouncing sound of reduction); (3) children aged ≤12 months; (4) treatment with the Pavlik harness or manual reduction and plaster fixation (for children less than 6 months of age, the Pavlik harness was adopted; for children aged 6-12 months or those in whom the Pavlik harness failed, manual reduction and plaster fixation were performed); (5) anteroposterior pelvic radiographs and MRI of the hip joint were performed after 3 weeks of treatment with the Pavlik harness or 1 day after manual reduction and plaster fixation, and the quality of images met the requirements of the study; (6) complete data.…”
Section: Study Subjectsmentioning
confidence: 99%
“…3,4,10e15 Most of the studies define failure of CR as the need for a subsequent OR following a re-dislocation. 16 Zhang et al, in their series of 138 hips treated by CR, reported a failure rate of 31% and concluded that age more than 18.35 months and IHDI Grade III & IV are more likely to fail with CR. 4 Schoenecker et al reported a successful CR in 68% of 38 hips, all of which were >18 months of age.…”
Section: Closed Reductionmentioning
confidence: 99%
“…Older age at reduction has been implicated in several studies as a cause of worse outcomes. Zhang et al specifically evaluated the impact of age following closed reduction [ 44 ]. They conducted a retrospective review of 107 patients with DDH, split into three groups based on age at reduction: < 12 months, 12–18 months and > 18 months.…”
Section: Complications With Open and Closed Reductionmentioning
confidence: 99%